Dosimetry in clinical static magnetic fields using plastic scintillation detectors - Stefanowicz, Sarah; Latzel, Harald; Lindvold, L. R.; Andersen, C. E.; Jäkel, Oliver; Greilich, Steffen (Radiation measurements, 2013)
To further improve the accuracy of dose delivery to the patient, several projects are pursuing the integration of linear accelerators with magnetic resonance imaging systems. Generally, this is conceived as the next generation of image-guided radiotherapy. For technical and physical reason it is, however, not clear yet how dosimetry will be conducted as standard methods and might not be easily transferred to systems with clinical magnetic fields. For dosimetry in MRI accelerators, we have tested plastic scintillation detectors (PSD) coupled to optical fibers. They are suitable for real-time and in-vivo dosimetry in radiation treatments and diagnostics and could be, being all-optical, promising candidates for this application. To study the basic feasibility of using PSDs with organic scintillators in magnetic fields, we measured the response of these dosimeters in presence of magnetic fields up to 1 T. In conclusion, we found some deviations up to 7% of the supposed signal. Although the scintillators are of much denser material, we measured the same behavior in signal as in (Meijsing et al., 2009) for a Farmer ionization chamber or as in (Raaijmakers et al., 2007) for films described which indicates radiation field effect rather than changes in the detected response itself.
Available online 28 March 2013
Gesehen am 15.02.2022